Environmental and Chemical Effects on Home Furnishings - Marie Hammer (EDIS)
This document is FCS 3156, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2002. First published: April 1990. Reviewed: August 2002.